RHETORIC AND IDEOLOGY: A CRITICAL DISCOURSE ANALYSIS OF ANIS BASWEDAN’S LECTURING SPEECH AT 2023 ST. LEE LECTURE – CAN DEMOCRACY DELIVER? REFLECTIONS ON THE INDONESIAN CASE - Hendra Husnussalam; Yana Yana (IKIP Siliwangi, 2024)
The purpose of this study is to explore Anis Baswedan’s ideology manifested in his lecturing speech at St. Lee Lecture delivered on March 6, 2023. The investigation of this study was conducted under Fairclough’s model of Critical Discourse Analysis (CDA). In understanding the ideology, the researchers worked on the microstructure level by employing Aristotle’s rhetoric theory in terms of components and devices. The results of this study revealed that, in related to persuasive elements used to support claims or respond to arguments, there are three components used, i.e., logos (50%), ethos (30%), and pathos (20%). In terms of conveying information, there are three devices employed, i.e., anaphora (50%), epistrophe (30%), and conduplicatio (20%). The analysis of rhetoric finally led to the findings of Baswedan’s ideology perspective towards the issues of emphasis on democratic accountability, challenges in democratic processes, reform focus, integration of political and bureaucratic processes, technocratic approach & delivery units, public-centered approach, infrastructure development for public welfare, negotiation & collaboration, and evaluation & adaptation.